Subcellular cell geometry on micropillars regulates stem cell differentiation. (December 2016) - Liu, Xiangnan; Liu, Ruili; Cao, Bin; Ye, Kai; Li, Shiyu; Gu, Yexin; Pan, Zhen; Ding, Jiandong
Abstract: While various material factors have been shown to influence cell behaviors, recent studies started to pay attention to the effects of some material cues on "subcellular" geometry of cells, such as self-deformation of cell nuclei. It is particularly interesting to examine whether a self deformation happens discontinuously like a first-order transition and whether subcellular geometry influences significantly the extent of stem cell differentiation. Herein we prepared a series of micropillar arrays of poly(lactide- co -glycolide) and discovered a first-order transition of nuclear shape as a function of micropillar height under the examined section area and interspacing of the pillars. The deformed state of the nuclei of mesenchymal stem cells (MSCs) was well maintained even after osteogenic or adipogenic induction for several days. The nuclear deformation on the micropillar arrays was accompanied with smaller projected areas of cells, but led to an enhanced osteogenesis and attenuated adipogenesis of the MSCs, which is different from the previously known relationship between morphology and differentiation of stem cells on flat substrates. Hence, the present study reveals that the geometry of cell nuclei may afford a new cue to regulate the lineage commitment of stem cells on the subcellular level.